Child care use and maternal labour supply: Evidence from Impacts of COVID-19 on Canadians [2020] - Zi, Yuyang (Université d'Ottawa | University of Ottawa, 2020)
This paper examines the impacts of COVID-19 on child care use and maternal labour supply in Canada. Using the data from Impacts of COVID-19 on Canadians - Parenting during the Pandemic [2020], I see sharp drops both in child care use and maternal labour supply during the quarantine and possibly when the lockdown is over . Meanwhile, mothers who have 0 - 5 years old children, university degrees, and immigrants show stronger dependence on child care services. Mothers with disabled children tend to spend more time helping their children with learning activities related to school.